Effect of cut-out shape on the stresses in aircraft wing ribs under aerodynamic load - Mohamed Ali, Jaffar Syed; W Embong, Wan Muhammad Hafizuddin; Aabid, Abdul (Penerbit Akademia Baru, 2021)
Ribs in aircraft wings maintain the airfoil shape of the wing under aerodynamic loads and also support the resulting bending and shear loads that act on the wing. Aircrafts are designed for least weight and hence the wings are made of hollow torsion box and the ribs are designed with cut-outs to reduce the weight of the aircraft structure. These cut-outs on the ribs will lead to higher stresses and stress concentration that can lead to failure of the aircraft structures. The stresses depend on the shape of the cut-outs in the ribs and thus in the present work, the commercial software ANSYS was used to evaluate the stresses on the ribs with different shapes of cut-outs. Four different shapes of cut-out were considered to study the effect of cut-out shape on the stresses in the ribs. It was found that the best shape for the cut-outs on the ribs of wings to reduce weight is elliptical.